Potential and Design for Head-Up Displays in Commercial Trucks - Dahlberg, Lukas; Eriksson, Märta; Hjelmgren, Viktor; Lundh, Alexander; Sahlin Wikström, Hampus; Weyler, Ebba (My University, 2025)
This thesis explores the potential with Augmented Reality Head-Up Displays (AR-HUDs) in commercial trucks, with a specific focus on the driver’s perspective. Through research and interviews, the project investigates if and how AR-HUDs can be used to enhance safety, usability, and personalisation in the truck. The report describes the development process and presents the outcome: a conceptual interface of an AR-HUD featuring different modes for different driving situations.